Problematika Peserta Didik Dalam Proses Pembelajaran Bahasa Arab Di Madrasah Aliyah Darul Qur’an Glenmore Banyuwangi - Ilham Nur Kholiq; Moh Zulkifli Khabibullah (Institut Agama Islam Darusssalam Blokagung, 2021)
This research will refer to the problems of students in the Arabic language learning process at Darul Qur'an High School Glenmore Banyuwangi. And the type of this research is qualitative research. In this study data collection was done by means of observation, interviews, and documentation. In this study interviewed students and teachers. The results of this study are; The problems of learning Arabic for students include: students lack the will to learn Arabic, environmental backgrounds that do not support progress in learning achievement, students lack confidence in Arabic lessons. The efforts made to overcome these problems include: the school is trying to improve welfare guarantees for educators, providing understanding and motivation to students, choosing appropriate and varied teaching methods, completing teaching and learning facilities and facilities, a teacher's understanding of the characteristics of participants. teach, and give assignments regularly.